What is happening to television news? - Nielsen, RK; Sambrook, R (Reuters Institute for the Study of Journalism, 2016)
Traditional television viewing is falling, and the rapid rise of online video viewing continues. If television news providers fail to respond to these profound shifts in how people use media, they risk eventually becoming irrelevant, a new report from the Reuters Institute for the Study of Journalism, University of Oxford warns.“There are no reasons to believe that a generation that has grown up with and enjoys digital, on-demand, social and mobile video viewing across a range of connected devices will come to prefer live, linear, scheduled programming tied to a single device just because they grow older,” says Dr Nielsen, Director of Research at the Reuters Institute. “This raises wider questions about how sustainable the broad public interest role broadcast news has played in many countries over the last 60 years is.” What's the solution? And what action should television news providers be taking to evolve effectively in a digital age? A new report by Rasmus Kleis Nielsen and Richard Sambrook explores what is happening to television news.